Cadmium and COD Removal from Municipal Wastewater Using Chlorella sp. Biomass in Microbial Fuel Cells - Agüero-Quiñones, Rickelmi (2023)
The increasing generation of wastewater with high levels of pollutants has become a serious environmental challenge. In this context, sustainable technologies are required to treat wastewater efficiently. Therefore, it was proposed to evaluate the effect of the biomass of Chlorella sp. on the removal of cadmium and chemical oxygen demand (COD) from municipal wastewater in the district of Urpay, Pataz, La Libertad, Peru, and the generation of electric power through single-chamber microbial fuel cells (MFC). An experimental design was applied, where nine treatments were carried out evaluating three doses of Chlorella sp. (10%, 20% and 30%) at pH values of 6.5, 7.0, and 7.5 of the residual water. Managing to generate peak current and voltage values of 4.61 mA and 1118.5 mV in the MFC at a pH of 7.5 with a dose of 30% of Chlorella sp., this same MFC managed to decrease concentrations of cadmium and COD by 97.5 and 15% in 25 and 15 days, respectively. This investigation demonstrated the importance of Chlorella sp. for the reduction in these two parameters, managing to provide a new method for the elimination of these pollutants in wastewater.